STRATEGI PENGAWAS DALAM PEMBINAAN KOMPETENSI PROFESIONALISME GURU (TRANSFORMASI KEPEMIMPINAN DAN MOTIVASI GURU SDN SUNGAI RAYA) - Yanti, Yovi; Anurrahman; Afandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research investigates strategies used by supervisors to enhance teachers' professional competencies related to leadership transformation and motivation at SD Sungai Raya, employing a qualitative approach with 10 participants (1 supervisor, 3 principals, 6 teachers). Data were collected through observation, interviews, and documentation, analyzed in three stages. Key findings include: (1) supervisors effectively enhance competencies by understanding teachers' needs, monitoring regularly, and providing motivation; (2) transformational leadership by principals fosters problem-solving and individual consideration, promoting experience sharing and recognition; (3) teachers exhibit discipline and increased motivation through positive colleague relationships. The study concludes that consistent collaboration among supervisors, principals, and teachers is crucial for improving educational quality.